Zanurzeni w mediach. Konteksty edukacji medialnej - Redakcja (Wydawnictwo Naukowe UAM, 2016)
Immersed in media. Contexts of media education is a book whose authors recognize the importance of the media in various areas of human activity. They specialize in educational science and media education. The texts included in the book make a substantial contribution to the devel-opment of research, and may become the first step towards further speculation and analysis in this field, as well as practical applications. The first part is devoted to various aspects of media education, including the media literacy of the contemporary human being. The second part refers to using media in educational practice, and the third to the media as a sphere of life for the contemporary human.

Autorzy monografii dostrzegają znaczenie mediów we wszystkich dziedzinach działalności człowieka. Pierwsza część poświęcona została różnym aspektom edukacji medialnej, w tym kompetencjom medialnym współczesnego człowieka. Druga dotyczy wykorzystania mediów w praktyce edukacyjnej, a ostatnia – mediów jako przestrzeni życia człowieka współczesnego.
Immersed in media. Contexts of media education
Keywords: media; działalność człowieka; edukacja medialna; wykorzystanie mediów